2023
DOI: 10.1503/cjs.009321
|View full text |Cite
|
Sign up to set email alerts
|

Parental-leave policies and perceptions of pregnancy during surgical residency training in North America: a scoping review

Abstract: Background: The number of surgical residents experiencing childbearing during residency training is increasing, and there is an absence of clarity with respect to parental-leave, lactation and return-to-work policies in support of residents. The aim of this review was to examine parental-leave policies during residency training in surgery and the perceptions of these policies by residents, program directors and coresidents, as described in the literature. Methods: We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Surgery as a specialty has historically been dominated by men, and gender disparities continue to be prevalent in this field (58)(59)(60). Many of the challenges that these women encounter are difficult to characterize through traditional quantitative methods (57,61); however, the biases described by women in this study, specifically those regarding pay inequities, parental norms and policies, increased administrative work, and referral biases, have received empirical support (43,(62)(63)(64)(65). The hesitation that women in this study described to address issues of gender equity for fear of judgment has also been captured in relation to other issues regarding gender discrimination, such as instances of sexual harassment and assault (66).…”
Section: Discussionmentioning
confidence: 86%
“…Surgery as a specialty has historically been dominated by men, and gender disparities continue to be prevalent in this field (58)(59)(60). Many of the challenges that these women encounter are difficult to characterize through traditional quantitative methods (57,61); however, the biases described by women in this study, specifically those regarding pay inequities, parental norms and policies, increased administrative work, and referral biases, have received empirical support (43,(62)(63)(64)(65). The hesitation that women in this study described to address issues of gender equity for fear of judgment has also been captured in relation to other issues regarding gender discrimination, such as instances of sexual harassment and assault (66).…”
Section: Discussionmentioning
confidence: 86%
“…They found that program directors and division chiefs were perceived to be more supportive of resident pregnancy in 2015 compared to 2008 [ 30 ]. One respondent in our study commented: “I am currently pregnant, and I am lucky to be in a residency program that is overall very supportive of parents, and it certainly has an influence on how well my pregnancy is going.” There must be greater institutional and collegial support for women to support their dual roles of both mothers and surgeons; with increased awareness, progress in policy and guideline development is under way [ 18 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since best practices recommend consistent scheduled pumping every 4 h, the majority of facilities cannot accommodate 30‐min pumping sessions, unless the facilities were close to the operating room, had industry quality breast feeding equipment, a storage area, and there was enough manpower to allow adequate coverage without disrupting surgical workflow [4, 5] All of this would also apply to the surgical trainee as the availability of extra manpower is certainly limited, timing during and in between surgeries when the trainees can excuse themselves to breast pump is unpredictable, and concern for feeling unsupported by fellow trainees and faculty is palpable. The reality of availability of onsite lactation facilities by only 58% of surgical program directors queried in North America is alarming [6]. Surgical trainees may find it difficult to leave the operating suite to pump, especially if the facility is too distant from the operating room and there is inadequate storage availability.…”
Section: Introductionmentioning
confidence: 99%